2009
DOI: 10.1375/brim.10.3.320
|View full text |Cite
|
Sign up to set email alerts
|

Planning Ability Following Moderate to Severe Traumatic Brain Injury: Performance on a 4-Disk Version of the Tower of London

Abstract: This study aimed to assess planning ability in adults with traumatic brain injury (TBI) using a 4-disk version of the Tower of London (TOL). Thirty three individuals with TBI were compared with equivalent numbers of matched controls. Overall, the TOL4 was shown to be sensitive to the effects of brain injury, with the TBI group performing significantly more poorly on this version of the planning test than the matched controls. More specifically, group differences were found to be related to the complexity of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 16 publications
3
34
0
3
Order By: Relevance
“…Our findings are in line with previous studies that have found deficits of efficiency in solving tower tasks in people with TBI (Chan et al, 2004;Shum et al, 2009). In contrast to some studies (Unterrainer et al, 2004), which have suggested that execution time is an important predictor of good performance on this test, in a multivariate analysis, our results suggest that TBI is associated most closely with the number of moves used, and not so much the time taken.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings are in line with previous studies that have found deficits of efficiency in solving tower tasks in people with TBI (Chan et al, 2004;Shum et al, 2009). In contrast to some studies (Unterrainer et al, 2004), which have suggested that execution time is an important predictor of good performance on this test, in a multivariate analysis, our results suggest that TBI is associated most closely with the number of moves used, and not so much the time taken.…”
Section: Discussionsupporting
confidence: 91%
“…Successful completion is thought to require multiple executive functions, including response inhibition, multi-step planning, and manipulation of information in working memory (Phillips, Wynn, Gilhooly, Della Sala, & Logie, 1999;Unterrainer et al, 2004). Studies have indicated that people with TBI often have deficits in performance on this type of task (Chan, Chen, Cheung, Chen, & Cheung, 2004;Shum et al, 2009). Electrophysiological and imaging analysis have further shown that this task is sensitive to lesions in the frontal lobe (Sullivan et al, 2009) and that people with TBI who perform poorly on tower tasks have weak activation in regions that are part of frontal/sub-cortical circuits (Cazalis et al, 2006;Rasmussen et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, the time to plan (time to first move) did not significantly decrease. Others have also noted that time to first move may not be a sensitive measure of planning [41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Čak i kod osoba sa nadprosečnom memorijom, jezičkim ili intelektualnim sposobnostima, problemi u domenu planiranja dovode do toga da im je potrebna podrška u svakodnevnom životu, jer nisu u stanju da organizuju i koordinišu svakodnevne aktivnosti. Teškoće u domenu planiranja su najuočljivije kod osoba sa lezijom prefrontalnog korteksa i kod osoba sa visokofunkcionalnim autizmom (Mackinlay et al, 2006;Shum et al, 2009), a identifikovane su i kod drugih kliničkih populacija, na primer, kod osoba sa shizofrenijom (Morris et al, 1995) i Parkinsonovom bolešću (Kostering et al, 2012, u štampi).…”
Section: Iz šKolske Dokumentacije Preuzeti Su Podaci O Uzrastu I Nivounclassified